Influences of ambient temperature, injection pressure and spray characteristics on ignition delay and combustion process of palm oil and waste cooking oil - Nursal, Ridwan Saputra; Jaat, Norrizam; Khalid, Amir; Ishak, Izuan Amin (2024)
Alternative fuels have been explored for the substitution of diesel to lessen dependence on fossil fuel and to mitigate environmental pollution. Opted on biodiesel seem like promising due to its availability and regenerability, as well as ability to lower emissions. The objective of this research is to investigate the effects of ambient temperature, injection characterirics and spray characteristics on ignition delay and combustion process of biodiesel blends derived from palm oil and waste cooking oil. The ignition delay and combustion were observed using a rapid compression machine with ambient temperatures ranging from 850 K to 1050 K and injection pressure ranging from 80 MPa to 130 MPa. Palm and waste cooking oil biodiesel blends fuel were produced by blending these oils with Euro5 pure diesel at concentration of 5vol%, 10vol% and 15vol% correspondingly. Higher injection pressure and higher ambient temperature have been found to significantly reduce the ignition delay and influences to the heat recovery of combustion, while the higher biodiesel blending concentration of biodiesel promotes the reduction of CO emissions